Formulation and Evaluation of Platelet Rich Plasma (PRP) Lotion Preparations with Asiaticoside as an Antioxidant - Mardhiani, Yanni Dhiani; Selifiana, Nita; Arna Ningsih1, Endah; Rusdiana, Taofik (Indonesian Journal of Pharmaceutics, 2023)
Currently, the use of PRP requires a person to visit a skin care clinic by doing a series of treatments directly. Therefore, in order to facilitate the use of PRP, asiaticoside lotion base products containing antioxidants can be used as a PRP product base. asiaticoside antioxidants serve to stabilize PRP when added to the base. This research uses Platelet-Rich Plasma (PRP) and Asiaticosida as active substances, Fancor® Uni-Embase as emollient and emulgator, DMDM hydantoin as preservative, and distilled water as carrier. The stages in this research include preparation of tools and materials, lotion base optimization, lotion preparation formulation, addition of active substances, lotion preparation evaluation, physical stability test, and antioxidant activity test. The results of the PRP lotion stability test with asiaticoside for 10 days showed significant results (p<0.05) which means that for 10 days there is a tendency to be unstable. Antioxidant activity test results obtained IC50 results on Asiaticosida of 57.63 µg/mL, on PRP of 196.1 µg/mL, on the base with the addition of Asiaticosida of 77.19 µg/mL, on F0 of 166.90 µg/mL, on F1 of 96.727 µg/mL, on F2 of 88.395 µg/mL, and on F3 of 82.017 µg/mL.Keywords: Lotion, PRP, asiaticoside, Antioxidant